ADAPTATION AND AGRICULTURAL STRATEGIES OF SOVIET KOREANS AFTER THE 1937 DEPORTATION - Ashurova Ulgozi Isroilovna (The Conference Hub, 2025)
The 1937 deportation of Koreans from the Soviet Far East to Central Asia marked a turning point in the ethnic and economic history of the USSR. Despite being uprooted from their homeland, the deported Koreans managed to reconstruct a productive agricultural system, transforming the harsh steppes of Kazakhstan and Uzbekistan into fertile lands. This paper analyzes the mechanisms of adaptation, collective work ethics, and the socio-economic role of Koreans in Soviet agricultural modernization, drawing on archival sources and recent historiography.
Keywords: Korean deportation; Soviet Far East; Central Asia; Uzbekistan SSR; collective farms; rice and vegetable cultivation; ethnic adaptation; socialist modernization; labour productivity; ethnic rehabilitation.